Automatic Real-Time Generation of Floor Plans Based on Squarified Treemaps Algorithm - Fernando Marson; Soraia Raupp Musse (International Journal of Computer Games Technology)
A novel approach to generate house floor plans with semantic information is presented. The basis of this model is the squarified treemaps algorithm. Previously, this algorithm has been used to create graphical representations based on hierarchical information, such as, directory structures and organization structures. Adapted to floor plans generation, this model allows the creation of internal house structures with information about their features and functionalities. The main contributions are related to the robustness, flexibility, and simplicity of the proposed approach to create floor plans in real-time. Results show that different and realistic floor plans can be created by adjusting a few parameters.